IEEE/ICME International Conference on Complex Medical Engineering 2010
DOI: 10.1109/iccme.2010.5558843
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of RFID systems on biotechnology insulin preparation: A study using HPLC and NMR spectroscopy

Abstract: The item-level traceability is a very important requirement for many practical application scenarios, where it needs to guarantee perfect transparency for products flow along the whole supply chain. Among these, the pharmaceutical distribution is a very interesting scenario, characterized by many challenges, where, the Radio Frequency Identification (RFID) technology will play a very important role. Unfortunately, there are still some technical barriers that are retarding the deployment of these innovative tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Studies exposing radiofrequency identification (RFID) systems, a similar technology to BLE but employing slightly different frequencies, have shown no alteration in the stereochemistry or molecular composition of xenobiotics. [ 1 , 2 ] Additionally, RFID is increasingly utilized in pharmaceutical manufacturing, underscoring the safety of using this technology near xenobiotics. [ 7 ]…”
Section: The Smart Naloxone Kitmentioning
confidence: 99%
“…Studies exposing radiofrequency identification (RFID) systems, a similar technology to BLE but employing slightly different frequencies, have shown no alteration in the stereochemistry or molecular composition of xenobiotics. [ 1 , 2 ] Additionally, RFID is increasingly utilized in pharmaceutical manufacturing, underscoring the safety of using this technology near xenobiotics. [ 7 ]…”
Section: The Smart Naloxone Kitmentioning
confidence: 99%
“…A theoretical concern that radiofrequencies may alter the chemical structure or alter the chiral composition of medications has remained unfounded. [14] Studies applying radiofrequency waves to insulin and chemotherapeutics have shown no effect in structural composition. [15, 16]…”
Section: The Mytmed Systemmentioning
confidence: 99%
“…A gelatin capsule can act as a barrier, preventing access to the gastric environment that dissolves and releases the drug. Activation of the RFID tag emits an ultra high-frequency (UHF) signal that may alter the molecular structure of drugs [26]. Several lines of evidence suggest that an RFID-tagged gelatin capsule overlying a medication will not alter the pharmacokinetics, pharmacodynamics, or structure of that drug.…”
Section: Potential Complications Of Ingestible Biosensors For Medicatmentioning
confidence: 99%